Development of downy mildew in grape bunches of susceptible and resistant cultivars: infection pathways and limited systemic spread. (26th April 2022) - Gindro, K.; Schnee, S.; Lecoultre, N.; Michellod, E.; Zufferey, V.; Spring, J.‐L.; Viret, O.; Dubuis, P.‐H.
Abstract: Background and Aims: Plasmopara viticola development in bunches of two grapevine cultivars, the resistant Divico and the susceptible Chasselas, was studied by using microscopy and molecular detection to investigate tissue susceptibility and the extent of colonisation. Methods and Results: Bunches were inoculated with P. viticola at four phenological stages, and the development of downy mildew was recorded. Visible symptoms were evident after the first three inoculation stages for Chasselas. Inoculation at inflorescence swelling resulted in the desiccation of the inflorescence and at the end of flowering led to desiccation of parts of the bunches with some berries developing normally until ripening. After inoculation of pea‐sized berries, brown rot symptoms appeared, whereas no infections were observed after inoculation at veraison. Histological and molecular examination showed that downy mildew invaded almost all bunch tissues but required an active stomata as an infection site. Mycelium and haustoria, however, were never observed in the vascular tissues. For Divico, inoculation at early stages of development resulted in sparse infections with limited colonisation. Conclusion: Downy mildew systemic development occurs only between adjacent tissues meaning that as the stomata lose function the severity of the infection is reduced. Significance of the Study: Limited infection justifies the maintenance of a fungicide control program for the resistant cultivar Divico.